Dean’s award dinner ceremony - Andrew, Leviana (Universiti Teknologi MARA, Sarawak, 2016)
The Dean’s Award Dinner Ceremony for the Bachelor in Office Systems Management (Hons.) (BM232) programme was held on 20 May 2016 at the GrandMargherita Hotel, Kuching. This dinner is held every semester to celebrate the success of students who achieve Grade Point Average (GPA) of 3.50 and above in the final examination. There were 55 recipients for the Dean’s Award and one recipient for the Vice-Chancellor Award, Miss Nor Diana Farehan Abu Bakar for the September 2015 — January 2016 semester. The semester 4 students are given the privilege to organise this event to give them the experience of planning and executing events on their own under the guidance of a lecturer. The event advisor this semester was Ms Leviana Andrew.